Diversity and composition of fungal communities across diverse environmental niches in Antarctica - Jiya, Namrata; Shede, Prafulla; Sharma, Avinash (Polar science, 2023)
Antarctica harbours a wide range of extreme and diverse ecological niches that support diverse group of microorganisms, making it important to investigate the microbial diversity of this pristine environment. The current study focuses on the diversity and distribution of fungi in diverse environmental niches like exposed soil, accumulated snow, deep sea, and lake sediments in the Larsemann Hills, Antarctica. Ascomycota (61.7%) was the most dominating phylum followed by Basidiomycota (31.1%), Chytridiomycota (5.7%) and Rozellomycota (1.4%). The families Camptobasidiaceae (23.1%), Cladosporiaceae (15.3%), Kriegeriaceae (8.2%), Mycosphaerellaceae (6.8%) and Helotiaceae (6.2%), while at the genus level Glaciozyma (24.8%), Cladosporium (16.8%), Phenoliferia (8.8%), Acrodontium (8%), and Aspergillus (5.4%) were highly prevalent. Interestingly, Austroplaca genus which is mostly indigenous to polar regions was exclusively detected in the accumulated snow sediments. Among the four heterogenous environments analyzed, lake sediments were shown to have a higher number of amplicon sequence variants (ASVs) than the other environments.